Unlocking the Strategy of Indonesian Government in Developing Digital Tourism - Susilo, Donny (MEC-J (Management and Economics Journal), 2020)
This study aims to understand to what extent the digital tourism development has been implemented by government of Indonesia and what strategies they use to reach that goal. Digitalization is an unavoidable change that has been influencing all aspect of people’s life, creating opportunity to digitalize tourism in Indonesia as one of main strategies in recovering economic performance post covid-19. The fact that tourism is one of the most significant sectors in Indonesia, urges local government to take significant role to ensure the digital tourism development is smoothly implemented. The novelty of this study lies in its exploration initiative on government strategies while study about digital tourism development is lacking. Content analysis was utilized to explore information from books, journals, interview report in newspaper and government website. The study revealed out that by utilizing partnership strategy with state-owned enterprises, start-ups and local people, government of Indonesia consistently prepares the infrastructure and incentive to support digitalization of its tourism in 4 main aspects which are digital distribution channel, digital promotion, digital payment and digital training.